2020
DOI: 10.3390/diagnostics10080557
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Hepatic Steatosis by Using the Double Nakagami Distribution: A Feasibility Study

Abstract: Ultrasound imaging is a first-line assessment tool for hepatic steatosis. Properties of tissue microstructures correlate with the statistical distribution of ultrasound backscattered signals, which can be described by the Nakagami distribution (a widely adopted approximation of backscattered statistics). The double Nakagami distribution (DND) model, which combines two Nakagami distributions, was recently proposed for using high-frequency ultrasound to analyze backscattered statistics corresponding to lipid dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
18
2
Order By: Relevance
“…Notably, as mentioned in Introduction, ultrasound parametric imaging using the Nakagami and HK distributions has been applied to clinical assessment of hepatic steatosis. It has been reported that the AUROCs for using Nakagami and HK imaging to detect hepatic steatosis ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} mild, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} moderate, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} severe) were (0.75, 0.82, 0.82) and (0.76, 0.80, 0.83), respectively [11] , [12] , which exhibits worse diagnostic performances compared with that of sample entropy imaging. The proposed sample entropy not only outperformed the statistical distribution parameters and Shannon entropy in characterizing hepatic steatosis but also provides the diagnostic ability in clinical fibrosis risk evaluations of individuals with developing hepatic steatosis, as supported by the current findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, as mentioned in Introduction, ultrasound parametric imaging using the Nakagami and HK distributions has been applied to clinical assessment of hepatic steatosis. It has been reported that the AUROCs for using Nakagami and HK imaging to detect hepatic steatosis ( \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} mild, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} moderate, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\ge $ \end{document} severe) were (0.75, 0.82, 0.82) and (0.76, 0.80, 0.83), respectively [11] , [12] , which exhibits worse diagnostic performances compared with that of sample entropy imaging. The proposed sample entropy not only outperformed the statistical distribution parameters and Shannon entropy in characterizing hepatic steatosis but also provides the diagnostic ability in clinical fibrosis risk evaluations of individuals with developing hepatic steatosis, as supported by the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the Nakagami and homodyned K (HK) distributions are the two primary general statistical models of ultrasound backscattering [9] . The progression of hepatic steatosis can be quantitatively described using these models with parameters estimated using raw envelope signals (before logarithmic compression) [10] [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, basic studies that use clinical data most commonly employ the Nakagami model. A wide variety of targets have been evaluated in such studies, including vascular studies by Huang [ 81 ], ophthalmology and breast cancer by Tsui [ 82 , 83 ], and the liver by Tsui and Yamaguchi [ 84 , 85 ]. In the most recent research, the Nakagami distribution has been applied to evaluating the temperature of living tissues by Hasegawa [ 86 , 87 ], and Tamura and Yamaguchi have combined multiple distributions to evaluate fat and fiber in the liver simultaneously [ 88 , 89 ].…”
Section: Amplitude Envelope Statisticsmentioning
confidence: 99%
“…Among different QUS parameters, scatterer number density has been found to be useful for different clinical applications such as liver fibrosis detection 2 and Hepatic steatosis assessment. 3 Scatterer number density can be quantified by modeling the ultrasound echo amplitude using different probability density functions. The homodyned K-distribution (HK-distribution) is a well-known distribution that has been widely used to quantify the scatterer number density and characterizing the tissues.…”
Section: Introductionmentioning
confidence: 99%